THE QUALITY OF COFFEE (Coffeasp) IN SOME DIFFERENT GEOGRAPHIC INDICATIONS : THE QUALITY OF COFFEE (Coffeasp) IN SOME DIFFERENT GEOGRAPHIC INDICATIONS - Harahap, Amir Mahmud; Siregar, Elda Sari; Lubis, Rafiqa Amanda; Srikumala, Indah (Jurnal Online Pertanian Tropik, 2022)
This study aims to determine the quality of coffee in several different geographical indications. This research was conducted at the Laboratory of the Faculty of Agriculture, University of Muhammadiyah South Tapanuli with a sampling method, namely sampling technique from 3 geographically indicated locations of coffee, namely Lintong Arabica Coffee, Mandailing Arabica Coffee and Sipirok Arabica Coffee. Observation parameters were altitude, water content, seed size and acidity (pH). Data analysis was carried out by analyzing the process hierarchy, correlation and concluded by descriptive method. Coffee quality is influenced by geographical indications, namely altitude. The highest water content is Mandailing Arabica Coffee and the lowest is Sipirok Arabica Coffee. The best bean size is Mandailing Arabica Coffee which has the highest size and the highest coffee acidity is Sipirok Arabica Coffee and the lowest is Lintong Arabica Coffee.